Optimizing construction parameters for fractured horizontal wells in shale oil - Liu, Xuewei; Li, Dongping; Jia, Yunpeng; Liyong, Yang; Xiaoting, Gou; Tao, Zhao; Ziwei, Chen; Mao, Li; Juan, Wang; Xiangyun, Sui; Donghua, Zhao; Hongxia, Tang; et al. (Frontiers in Earth Science, 2023)
Shale oil is mainly extracted by fracturing, but it is difficult to determine the optimization construction parameters to obtain maximum productivity. In this paper, a fuzzy comprehensive production evaluation model for fractured shale oil horizontal wells based on random forest algorithm and coordinated principal component analysis is proposed, and the fracturing parameters of target wells are optimized by combining with orthogonal experimental design. The random forest algorithm was used to calculate the importance of data sample factors, and the main controlling factors of the production of fractured horizontal wells in shale oil were obtained. Principal component analysis was used to reduce the dimension of main control factors to reduce the noise of sample data. Furthermore, random forest algorithm was used to determine the weight of principal components after dimensionality reduction. The membership function of the main control factors after dimensionality reduction was established by combining fuzzy statistics method and assignment method, and the membership matrix of the effect prediction of fractured horizontal wells in shale oil was determined. The fuzzy comprehensive evaluation method is used to score and evaluate the effect of fractured horizontal wells. Combined with the orthogonal experimental design method, the parameter optimization design of fractured horizontal well considering the comprehensive action of multiple parameters is realized. After construction according to the optimized parameters, the production after fracturing increases significantly, which verifies the optimization method rationality proposed in this paper.